Finite mathematics / lb Howard L. Rolf. - Rolf, Howard Leroy (Dubuque, Iowa : Wm. C. Brown, 1994)
Get the background you need and discover the usefulness of mathematics in analyzing and solving problems with FINITE MATHEMATICS, 8th Edition. The author clearly explains concepts, and the computations demonstrate enough detail to allow you to follow and learn steps in the problem-solving process. Hundreds of examples and exercises, many based on real-world data, illustrate the practical applications of mathematical concepts. The book also includes technology guidelines to help you successfully use graphing calculators and Microsoft Excel to solve selected exercises.
function and lines -- linear systems -- linear programming -- linear programming :the simplex method -- sets and counting -- probability -- statics -- mathematics of finance -- game theory.
Includes index.
1
Keywords: Mathematics